Governments, Parliaments and Legislative Activity*. Issue 3 (6th July 2015) - Bräuninger, Thomas; Debus, Marc; Wüst, Fabian
Abstract : Various strands of literature in comparative politics suggest that there is a differential impact of the type of government and their supporting legislative coalitions in parliamentary democracies, for example, in terms of their size and ideological heterogeneity, and on their potential to induce policy change. Most studies in this area focus on governments as agenda-setters, possibly neglecting the role of parliaments as a further key actor in policy making. In this article, we address the broader question as to how patterns of conflict within parliament effect legislative activity of governments and parliamentary actors. Through a simultaneous analysis of the success and event history of over 12, 000 legislative bills in three parliamentary systems and one semi-presidential system from 1986 until 2003, we show how the interplay of actor motivations and institutional settings has a discriminating impact on the potential of both the government and parliament to induce policy change.